Two Visually Meaningful Correlation Measures for Comparing Calculated and Measured Response Histories - Benjamin Whang; William E. Gilbert; Stephen Zilliacus (Shock and Vibration)
Two visually meaningful correlation measures are proposed for comparing calculated and measured response histories. One is an error index which is a simplification of RSS (root-sum-square) error factor, and the other is an inequality index that is a simplification of Theil’s inequality coefficient. The first compares the difference between the calculated and the measured histories to the measured history. The second compares the difference between the two histories to the sum of the two. The proposed correlation measures are compared to other existing measures, namely, Geers’ Error Factors, RSS Error Factor, and Theil's Inequality Coefficient for ease of interpretation and visualization.